UTILIZATION OF XENOGRAFT AS A BONE REGENERATION SCAFFOLD FOR RIDGE PRESERVATION: A CASE REPORT - Putra, Mardikacandra Manggala; Tadjoedin, Fatimah Maria; Masulili, Sri Lelyati C.; Widaryono, Adityo (Universitas Baiturrahmah, 2023)
Introduction: Ridge preservation is a periodontal surgical treatment that has an important role in the long-term success of dental implants. An adequate alveolar bone dimension makes future implant placement more predictable. Xenograft is being used as filler material in ridge preservation following tooth extraction, due to osteoconductive and slow-resorbing properties. Patient’s dental impressions and radiographs pre- and post-treatment ridge preservation were used to evaluate the alveolar ridge dimensions. This case report aimed to evaluate of ridge preservation treatment using xenograft material in an open wound healing approach. Patient’s main concerns: A 58-year-old male patient referred from the conservation department was undergoing root canal treatment of his right lower molars and wanted to make a fixed denture. Important clinical findings: Tooth 46 had mobility grade 2, probing pocket depth of 12 mm, and clinical attachment loss of 11 mm. Primary diagnoses: Other conditions affecting the periodontium et causa endodontic-periodontal lesions. Interventions and outcomes: Tooth 46 were extracted with minimal tissue trauma and followed with ridge preservation using xenograft. The collagen membrane was immobilized with the combination figure of eight and simple interrupted suturing technique in open wound healing approach. The purpose of ridge preservation is to prevent of alveolar bone resorption and prepare alveolar dimension for dental implant placement. Xenograft plays an important role as a scaffold in regenerating alveolar bone. Conclusion: Xenograft effectively regenerates new bone in ridge preservation to prepare an implant placement. Periodic control and long-term evaluation are needed to evaluate the success of this treatment.